Mimetic pressures influencing mandatory disclosure of local government financial statements in Indonesia - Arifin, J.; Tower, Greg; Porter, Stacey (Wiley, 2012)
This study examines the level of mandatory disclosure within financial statements of Indonesian local governments. Indonesia is a developing country that has recently undergone major state financial reform. Isomorphic institutional theory is adopted as the underlying theoretical framework. There is a moderate level of Government Compliance Index (49.9%). The highest level of communication is on issues related to Information on Fiscal Policy (81.2%). Whereas the lowest level of communication is on the Information of Macro Economy (33.6%). Regression analysis shows that the mimetic isomorphism variables, measured by using jurisdiction variables, are positive and significant predictors of the extent of mandatory disclosure. Local governments that are located in Java disclose more than non-Java, local governments which have higher Human Development Index disclose better than the lower score, and the significance of age of local governments imply that older local governments had more experience in dealing with and communicating their mandatory disclosures.